Salt stress affects the bacterial communities in rhizosphere soil of rice - Zhou, Yujie; He, Zhizhou; Lin, Qiuyun; Lin, Yuehui; Long, Kaiyi; Xie, Zhenyu; Hu, Wei (Frontiers in Microbiology, 2024)
Salt is a primary factor limiting the utilization of saline lands in coastal beach areas, with rhizosphere microorganisms playing a crucial role in enhancing crop stress resistance and exhibiting high sensitivity to environmental changes. Rice (Oryza sativa L.) is the preferred crop for reclaiming salinized soils. This study determined the microbial communities in rhizosphere soil of rice under different salt stress treatments by high-throughput sequencing. We found that salt stress changed the bacterial community diversity, structure and function in rhizosphere soil of rice. Salt stress significantly reduced the richness and diversity of bacterial communities in rhizosphere soil of rice. The bacterial community was characterized by higher abundance of the phyla Chloroflexi, Proteobacteria and Actinobacteria; the relative abundances of Firmicutes, Acidobacteriota and Myxococcota were decreased, while Bacteroidota and Cyanobacteria were increased under salt stress. The functions of bacterial communities in rhizosphere soil of rice mainly include chemoheterotrophy, aerobic_chemoheterotrophy, phototrophy etc., chemoheterotrophy and aerobic_chemoheterotrophy were significantly higher NS3 (adding 3‰ NaCl solution to the base soil) treatment than NS6 (adding 6‰ NaCl solution to the base soil) treatment. These findings provide a theoretical foundation for the development of specialized salt-tolerant microbial agents for rice cultivation and offer a viable strategy for improving the soil environment of saline coastal lands through the application of beneficial microorganisms.